Respuesta :
x - (9x - 10) + 11 = 12x + 3(-2x + [tex] \frac{1}{3} [/tex] ) equals x = [tex] \frac{10}{7} [/tex] .
First, simplify brackets. / Your problem should look like: x - 9x + 10 + 11 = 12x + 3(-2x + [tex] \frac{1}{3} [/tex] ).
Second, simplify x - 9x + 10 + 11 to -8x + 10 + 11. / Your problem should look like: -8x + 10 + 11 = 12x + 3(-2x + [tex] \frac{1}{3} [/tex] ).
Third, simplify -8x + 10 + 11 to -8x + 21. / Your problem should look like: -8x + 21 = 12x + 3(-2x + [tex] \frac{1}{3} [/tex] ).
Fourth, expand. / Your problem should look like: -8x + 21 = 12x - 6x + 1.
Fifth, simplify 12x - 6x + 1 to 6x + 1./ Your problem should look like: -8x + 21 = 6x + 1.
Sixth, add 8x to both sides. / Your problem should look like: 21 = 6x + 1 + 8x.
Seventh, simplify 6x + 1 + 8x to 14x + 1. / Your problem should look like: 21 = 14x + 1.
Eighth, subtract 1 from both sides. / Your problem should look like: 21 - 1 = 14x.
Ninth, simplify 21 - 1 to 20. / Your problem should look like: 20 = 14x.
Tenth, divide both sides by 14. / Your problem should look like: [tex] \frac{20}{14} [/tex] = x.
Eleventh, simplify [tex] \frac{20}{14} [/tex] to [tex] \frac{ 10}{7} [/tex] . / Your problem should look like: [tex] \frac{10}{7} [/tex] = x.
Twelfth, switch sides. / Your problem should look like: x = [tex] \frac{10}{7} [/tex] which is your answer.
First, simplify brackets. / Your problem should look like: x - 9x + 10 + 11 = 12x + 3(-2x + [tex] \frac{1}{3} [/tex] ).
Second, simplify x - 9x + 10 + 11 to -8x + 10 + 11. / Your problem should look like: -8x + 10 + 11 = 12x + 3(-2x + [tex] \frac{1}{3} [/tex] ).
Third, simplify -8x + 10 + 11 to -8x + 21. / Your problem should look like: -8x + 21 = 12x + 3(-2x + [tex] \frac{1}{3} [/tex] ).
Fourth, expand. / Your problem should look like: -8x + 21 = 12x - 6x + 1.
Fifth, simplify 12x - 6x + 1 to 6x + 1./ Your problem should look like: -8x + 21 = 6x + 1.
Sixth, add 8x to both sides. / Your problem should look like: 21 = 6x + 1 + 8x.
Seventh, simplify 6x + 1 + 8x to 14x + 1. / Your problem should look like: 21 = 14x + 1.
Eighth, subtract 1 from both sides. / Your problem should look like: 21 - 1 = 14x.
Ninth, simplify 21 - 1 to 20. / Your problem should look like: 20 = 14x.
Tenth, divide both sides by 14. / Your problem should look like: [tex] \frac{20}{14} [/tex] = x.
Eleventh, simplify [tex] \frac{20}{14} [/tex] to [tex] \frac{ 10}{7} [/tex] . / Your problem should look like: [tex] \frac{10}{7} [/tex] = x.
Twelfth, switch sides. / Your problem should look like: x = [tex] \frac{10}{7} [/tex] which is your answer.